2003
DOI: 10.1590/s0100-40422003000600021
|View full text |Cite
|
Sign up to set email alerts
|

Sucroquímica: síntese e potencialidades de aplicações de alguns derivados químicos de sacarose

Abstract: Recebido em 13/8/02; aceito em 19/5/03 SUCROCHEMISTRY: SYNTHESIS AND POTENTIALITIES FOR APPLICATIONS OF SOME SUCROSE CHEMICAL DERIVATIVES. The interest on the use of sucrose as raw material increased in the last years. In this work, the synthesis and applications of sucrose derivatives as esters, ethers, and other products are discussed in a concise manner aiming to presenting the sucrochemistry as a promising field in organic chemistry from a rather accessible, low-priced, ecological, and renewable source.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 38 publications
0
1
0
4
Order By: Relevance
“…Em particular, a sacarose ou 1-O-( -D-Frutofuranosil)--D-glicopiranose (Fig. 3b), por ser um poliol pode reagir ou se associar de maneira similar aos álcoois (BOSCOLO, 2003;BETTELHEIM et. al., 2012).…”
Section: Resultsunclassified
“…Em particular, a sacarose ou 1-O-( -D-Frutofuranosil)--D-glicopiranose (Fig. 3b), por ser um poliol pode reagir ou se associar de maneira similar aos álcoois (BOSCOLO, 2003;BETTELHEIM et. al., 2012).…”
Section: Resultsunclassified
“…It is suggested that this phenomenon involves the presence of acyl group, donor of saccharides ester that can modify the physiological function of the bacteria[71]. Studies revealed that the action of sucrose-ester on bacteria do not appear to occur by solubilizing the cell membrane, but due to a autolytic enzymatic stimulus, called bacterial autolysis[72,73]. The results of the present study demonstrate, especially for the sucrose-based monomers, that the metabolic activity of S. mutans decreases in the presence of saccharides, and the effect is sustainable for at least the short period of incubation used in this study (5 days).…”
Section: Discussionmentioning
confidence: 99%
“…Baseado em suas observações e em seu conhecimento das pesquisas realizadas, o cientista constatou a existência de sacarina (11). Apresentando o nome químico 1,1-dioxo-1,2-benzotiazol-3-ona, a substância sacarina (11) é um derivado sulfonamídico do tolueno (52). É comumente utilizada em refrigerantes, assados, geleias, chicletes, doces, vitaminas, medicamentos, produtos cosméticos (pasta de dente, enxaguatório bucal e brilho labial).…”
Section: Sacarinaunclassified